Psychoeducational Intervention Benefits the Quality of Life of Patients with Active Systemic Lupus Erythematosus. (26th May 2021) - Xu, Hongyan; Teng, Qiao; Zeng, Yan; Tian, Chunping; Yang, Bowen; Yao, Xiaoling
Abstract : Objectives . Systemic lupus erythematosus (SLE) is a complex and relapsing autoimmune disease and worsens the quality of life (QOL) of patients by affecting their physical and psychological status. The effectiveness of psychoeducational interventions on patients with active SLE was investigated. Methods . Eight-five patients with active SLE were randomly assigned to an observation group or a control group; patients in the observation group received psychoeducational interventions. The following variables were evaluated within a week after admission, 3 and 6 months after psychoeducational intervention: the World Health Organization Quality of Life Instrument- (WHOQOL-) BREF scores, the Medical Outcomes Study Short Form 36 (SF-36) scores, the Beck Depression Inventory, and Spielberger's State-Trait Anxiety Inventory (STAI). Results . We found that scores of all four domains of the WHOQOL-BREF scale were remarkably increased 3 months after psychoeducational intervention in the intervention group and significantly higher than the control group (P < 0.05 ); 6 months after psychoeducational intervention, psychological and social domain scores of the WHOQOL-BREF scale were remarkably higher in the intervention group than those in the control group, while other scores of three domains were not. PF, RP, BP, GH, RE, and MH scores of the SF-36 scale were remarkably increased 3 months after psychoeducational intervention in the intervention group rather than VT and SF, while all scores of subscales were notably higher in the intervention group than those in the control group (P < 0.05 ). Six months after psychoeducational intervention, PF, RP, BP, GH, and RE scores of the SF-36 scale were remarkably higher in the intervention group than those in the control group, while VT, SF, and MH scores were not. Three months after psychoeducational intervention, the levels of depression and anxiety of SLE patients were reduced and significantly lower than those in the control group (P < 0.05 ). Six months after psychoeducational intervention, the level of depression was still reduced, while the level of anxiety was not. Compared with the control group, the levels of depression and anxiety of SLE patients were remarkably declined in the observation group 6 months after psychoeducational intervention (P < 0.05 ). Conclusion . These data suggest psychoeducational interventions can significantly improve and maintain the QOL of patients with active SLE.